Burden, trends, and predictions of low physical activity-related diseases in China: analysis from the Global Burden of Disease Study, 1990–2021, with projections to 2035 - Zhang, Chuan; Chen, Quanzheng; Yin, Fuqiang; Qin, Lanyan; Zhang, Shuna (Frontiers in Public Health, 2025)
ObjectiveTo evaluate the burden of disease related to low physical activity in China, examine its trends over time, and predict future trends up to 2035 to inform preventive actions.MethodsUsing Global Burden of Disease Study 2021 (GBD2021) data, we analyzed the burden of disease associated with low physical activity, employing Deaths and Disability-Adjusted Life Years (DALYs) as indicators. Trends from 1990 to 2021 were examined using the Estimated Annual Percentage Change (EAPC) method, and future projections were made using the BAPC model.ResultsThe number of deaths attributable to low physical activity rose from 48,882 in 1990 to 148,152 in 2021, with the age-standardized death rate decreasing slightly from 8.39 to 8.18 per 100,000 (EAPC = 0.07). DALYs increased from 1,246,888 to 3,254,644, while the age-standardized DALYs rate fell from 168.93 to 162.52 per 100,000 (EAPC = −0.08). The DALY rate for diabetes increased from 30.12 to 36.54 per 100,000 (EAPC = 0.42); ischemic heart disease death rate rose from 2.86 to 3.52 per 100,000 (EAPC = 1.12), and the DALY rate increased from 40.72 to 46.05 per 100,000 (EAPC = 0.8). The highest death and DALY rates were observed in individuals over 95 years old. Females had higher death and DALY rates than males, with a death rate of 8.29 per 100,000 and a DALY rate of 197.98 in 2021. The BAPC model predicts that by 2035, deaths will reach 161,280 and DALYs will reach 3,523,135.ConclusionFrom 1990 to 2021, the age-standardized death and DALY rates associated with low physical activity in China declined, yet the absolute number of deaths and DALYs increased due to population growth and aging. Special attention is needed for diabetes and ischemic heart disease, as their burdens have significantly risen. Although females are more affected by low physical activity than males, the increase in the burden among males has been more pronounced in recent years. The impact of low physical activity intensifies with age, particularly among the older adult. Thus, targeted strategies are essential to mitigate the burden of low physical activity in China.